1999
DOI: 10.1016/s0022-2275(20)32451-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of synthetic saponin cholesterol absorption inhibitors in rabbits: evidence for a non-stoichiometric, intestinal mechanism of action

Abstract: The hypocholesterolemic activities of pamaqueside and tiqueside, two structurally similar saponins, were evaluated in cholesterol-fed rabbits. The pharmacological profiles of the saponins were virtually identical: both dosedependently decreased the intestinal absorption of labeled cholesterol 25-75%, increased fecal neutral sterol excretion up to 2.5-fold, and decreased hepatic cholesterol content 10-55%. High doses of pamaqueside ( Ͼ 5 mg/kg) or tiqueside ( Ͼ 125 mg/kg) completely prevented hypercholesterolem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(9 citation statements)
references
References 43 publications
2
7
0
Order By: Relevance
“…Also, saponins could lessen the cholesterol captivation and ease neuter sterols emission (Jenkins and Atwal, 1994), that lessening it absorption and hepatic substance. The current results showed that YS saponins attenuated serum cholesterol and agreed with Aslan et al (2004) in laying hens and Morehouse et al (1999) in rabbits. Cholesterol level was diminished by adding 120 mg YS/kg for laying hens diet (Kutlu et al, 2001).…”
Section: Blood Constituentssupporting
confidence: 92%
“…Also, saponins could lessen the cholesterol captivation and ease neuter sterols emission (Jenkins and Atwal, 1994), that lessening it absorption and hepatic substance. The current results showed that YS saponins attenuated serum cholesterol and agreed with Aslan et al (2004) in laying hens and Morehouse et al (1999) in rabbits. Cholesterol level was diminished by adding 120 mg YS/kg for laying hens diet (Kutlu et al, 2001).…”
Section: Blood Constituentssupporting
confidence: 92%
“…A number of studies, such as those of Malinow et al (1977), have shown that alfalfa saponins have hypocholesterolemic activity in nonhuman primates. A number of synthetic saponins have been shown to be cholesterol absorption inhibitors (Harwood et al, 1993;Morehouse et al, 1999), causing reduction in plasma low-density-lipoprotein cholesterol fractions. Although it is generally accepted that the principal action of saponins on blood cholesterol is by sequestration of cholesterol and bile acids in the intestine, thus preventing the cholesterol from being recycled again into the blood stream again (Cheeke and Otero ( 2005) and Cheeke et al, (2006).…”
Section: Resultsmentioning
confidence: 99%
“…By inhibiting the enzyme 3-hydroxy-3-Metilglutaril-CoA (HMG-CoA reductase), which plays a role in cholesterol synthesis, as well as the LDL receptor through SERBP, flavonoids and essential oils can decrease cholesterol biosynthesis and absorption (Sunarto, 2012;Lovita, 2013 andAbdel-Azeem &Basyony, 2019). Saponins and tannins also have a role in cholesterol uptake suppression by inhibiting lipase activity, binding cholesterol, and lowering surface tension by the action of saponin binding cholesterol in the gut lumen, which influences fat metabolism in the body (Morehouse et al, 1999). Table (5) shows the effect of galangal supplements on antioxidant levels in the blood serum of treated broiler chicks.…”
Section: Discussionmentioning
confidence: 99%